Konflik Antara Penerapan Undang-Undang Perlindungan Anak Dengan Penegakan Kedisiplinan Sekolah - Mursalina, Siti Ari; Zulfah, Zulfah; Nurkolis, Nurkolis (Cetta: Jurnal Ilmu Pendidikan, 2025)
The implementation of the Child Protection Act in schools has had a significant impact on disciplinary practices. This policy encourages schools to exercise greater caution in imposing sanctions, especially those involving physical and verbal actions that could be categorized as violence. The background of this study is the emerging dilemma faced by teachers in balancing the enforcement of school regulations while avoiding legal violations, resulting in anxiety when taking disciplinary action and increasing conflicts such as parental protests and reports to authorities. This study aims to analyze the impact of the Child Protection Act on school disciplinary practices and offer resolution strategies. A descriptive qualitative method was employed, using in-depth interviews, observations, and document studies conducted in several primary and secondary schools. The results show that the implementation of the law has created an imbalance between teacher authority and children's rights, complicating classroom management dynamics. Many schools have subsequently revised their codes of conduct to align with child protection principles. The study concludes that there is a need for discipline approaches based on guidance and respect for children's rights, intensive teacher training in positive discipline, and the development of additional regulations that proportionally protect the role of educators. Collaboration among teachers, parents, and policymakers is crucial to establishing a disciplinary system that is fair, educational, and consistent with the protection of children's rights.